THE EFFECT OF CHRONIC IMMOBILIZATION STRESS ON THE CONTENT OF MICRO- AND MACROELEMENTS IN THE PANCREAS AND BLOOD SERUM OF RATS AND THEIR NEWBORN OFFSPRING - Павлова, Олена; Сіренко, Віктор (SWorldJournal, 2023)
Have been considered the role of macro- and microelements - Ca, Mg, Zn, Fe, and Cu imbalance in the blood serum and pancreatic tissue homogenate of rats, whose pregnancy took place against the background of chronic immobilization stress and their newborn